2002
DOI: 10.1086/342924
|View full text |Cite
|
Sign up to set email alerts
|

s‐Process Nucleosynthesis in Carbon Stars

Abstract: We present the first detailed and homogeneous analysis of the s-element content in Galactic carbon stars of N-type. Abundances of Sr,Y, Zr (low-mass selements, or ls) and of Ba, La, Nd, Sm and Ce (high-mass s-elements, hs) are derived using the spectral synthesis technique from high-resolution spectra. The N-stars analyzed are of nearly solar metallicity and show moderate s-element enhancements, similar to those found in S stars, but smaller than those found in the only previous similar study (Utsumi 1985), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
258
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(294 citation statements)
references
References 74 publications
(74 reference statements)
31
258
5
Order By: Relevance
“…3), owing to the higher temperatures attained by these stars. Moreover, the expected surface s-process distributions of intermediate AGB stars are characterized by low or even negative [hs/ls] indexes and high [Rb/Sr] ratios, in striking contrast to the observed spectra (Abia et al 2002).…”
Section: Introductioncontrasting
confidence: 67%
See 1 more Smart Citation
“…3), owing to the higher temperatures attained by these stars. Moreover, the expected surface s-process distributions of intermediate AGB stars are characterized by low or even negative [hs/ls] indexes and high [Rb/Sr] ratios, in striking contrast to the observed spectra (Abia et al 2002).…”
Section: Introductioncontrasting
confidence: 67%
“…This model is representative of low-mass AGB stars, i.e. the most promising candidates to reproduce the majority of the observed s-process distributions in AGB stars (see, e.g., Abia et al 2002). Very similar results can be obtained for different metallicities or slightly different masses (in the range 1.5−2.5 M ).…”
Section: Introductionsupporting
confidence: 56%
“…This choice corresponds to 4 × 10 −6 M ⊙ of 13 C in LMS and to 4 × 10 −7 M ⊙ of 13 C in IMS (see Section 3). We note that the existence of a wide intrinsic spread of 13 C concentrations, from a few 10 −6 M ⊙ down to the complete absence of the 13 C pocket in the intershell zone, is demonstrated by observations of a wide range of s-process enhancements at a given metallicity in AGB stars [205] [206] [207]. This is also shown by the isotopic patterns in presolar grains (see e.g.…”
Section: What Do Agb Stars Produce?supporting
confidence: 53%
“…This is mainly 12 C as the primary product of the triple alpha reaction, but also the products of neutron-capture synthesis. There are two main neutron sources in AGB stars: 1) the 22 Ne(α, n) 25 Mg reaction which is activated at temperatures of T 300 × 10 6 K, and 2) the 13 C(α, n) 16 O reaction, which is activated at much lower temperatures of T 90 × 10 6 K. Observational and theoretical evidence has shown that the 13 C(α, n) 16 O reaction is the main neutron source in low-mass AGB stars of ≈1−3 M (Straniero et al 1995;Gallino et al 1998;Abia et al 2002).…”
Section: Introductionmentioning
confidence: 99%